Establishing Halomonas as a chassis for industrial biotechnology: advances in synthetic biology tool development and metabolic engineering strategies - André A. B. Coimbra; Satya Prakash; José I. Jiménez; Leonardo Rios-Solis (Microbial Cell Factories)
Abstract Background Halomonas species have recently emerged as promising chassis organisms for next-generation industrial biotechnology, due to their ability to thrive under high-salt conditions, where most microorganisms cannot survive. This feature minimizes contamination risks, thus enabling cultivation under open, unsterile conditions. In addition, many Halomonas species naturally produce large amounts of the bioplastic polyhydroxybutyrate and the high-value osmolyte ectoine. Main text This review explores the development of genetic manipulation tools and their pivotal role in establishing the genus Halomonas as an industrial chassis. Key additions to the synthetic biology toolbox, including cloning vectors, genetic parts, and genome editing systems are highlighted, along with challenges faced for their adoption, such as difficulties in transformation. In addition, we showcase how these tools have been employed for the development of more robust, high-producing strains through metabolic engineering, as well as for expanding the portfolio of target metabolites produced by Halomonas. Conclusion Recent developments in synthetic biology tools and metabolic engineering highlighted in this review underscore the potential of Halomonas for large scale metabolite production and provide a promising outlook towards their role as a microbial chassis in industrial biotechnology.